2013
DOI: 10.1021/jp4077036
|View full text |Cite
|
Sign up to set email alerts
|

Rotational Spectrum and Structure of Cyclohexene Oxide and the Argon–Cyclohexene Oxide van der Waals Complex

Abstract: The rotational spectra of cyclohexene oxide and its van der Waals complex with argon have been observed with a Balle-Flygare type pulsed jet Fourier transform microwave spectrometer in the 6 to 20 GHz region. This work improves the existing rotational and quartic centrifugal distortion constants of cyclohexene oxide, its six singly substituted (13)C, and the (18)O isotopologue. In addition, the (17)O isotopologue was observed in natural abundance. The quadrupole coupling constants for the (17)O isotopologue ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…We have determined that the argon occupies a position above the ring and on the opposite side of the epoxide in both the five-membered ring, cyclopentene oxide (CPO), 9 and the six-membered ring, cyclohexene oxide. 10 In the argon−cyclobutanone complex, 11 we found that the argon is in van der Waals (vdWs) contact with the carbonyl carbon but not the oxygen. Argon is further back on the ring and just inside the positively charged hydrogen on one of the equivalent cross-ring carbons.…”
Section: ■ Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…We have determined that the argon occupies a position above the ring and on the opposite side of the epoxide in both the five-membered ring, cyclopentene oxide (CPO), 9 and the six-membered ring, cyclohexene oxide. 10 In the argon−cyclobutanone complex, 11 we found that the argon is in van der Waals (vdWs) contact with the carbonyl carbon but not the oxygen. Argon is further back on the ring and just inside the positively charged hydrogen on one of the equivalent cross-ring carbons.…”
Section: ■ Introductionmentioning
confidence: 95%
“…Microwave structural studies using numerous isotopologues of the monomer ring compounds and their rare gas complexes allow us to determine the site on the host ring at which the rare gas forms a van der Waals bond. We have determined that the argon occupies a position above the ring and on the opposite side of the epoxide in both the five-membered ring, cyclopentene oxide (CPO), and the six-membered ring, cyclohexene oxide . In the argon–cyclobutanone complex, we found that the argon is in van der Waals (vdWs) contact with the carbonyl carbon but not the oxygen.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation